URGENSI KAJIAN HADIS DI INDONESIA : Pemikiran M. Syuhudi Ismail dan Ali Mustafa Ya’qub - Khotimah, Husnul (DIRAYAH : Jurnal Ilmu Hadis, 2023)
Efforts to study hadith have been carried out by scholars since the time of the Companions until now. From him, various works emerged, ranging from the codification of hadith by earlier scholars to criticisms of the originality of hadith by orientalist scholars. This study was later developed in Indonesia. In the discourse of contemporary hadith studies in Indonesia, several names are M. Shuhudi Ismail and Ali Mustafa Yaqub. They are hadith scholar in Indonesia who is quite respected and his credibility and intellectuality are taken into account. This article presents the offer, method, and contribution of M. Syuhudi Ismail in the Development of Hadith Studies in Indonesia as well as criticism of problematic hadiths & Ali Mustofa Yaqub's contribution to the development of hadith studies in Indonesia. The method that the author uses is library research or library research with data sources in the form of writings from previous research related to the theme being discussed.